(untitled) (East West Medical College Journal, 2024)
Most of the students considered neuroanatomy to be a difficult subject that contains a large volume of information. Therefore, many of them have the tendency to memorise the subject rather than understanding. The learning will be permanent if learning and its assessment is structured around generalisable rules or ‘principle’ rather than trying to memorise plenty of apparently disconnected ‘information’. Materials and methods: The Neuroanatomy portion of the Anatomy question papers of the First Professional MBBS Examinations of four public universities were analysed. It was a cross sectional, observational study carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2012 to December 2012. Results: The analyses of written question papers revealed that a vast majority (85.40 ± 7.32%) of the question segments in the question papers of four public universities were ‘Information-based segments’. The mean proportion (±SD) of ‘principle-based segments’ was 14.60 ± 7.32%. Conclusion: The results of present study provide a baseline data on the relative proportion of ‘principle-based questions’ and ‘information-based questions’ in the Neuroanatomy portion of Anatomy question papers of four public universities in Bangladesh. The study also suggests that the issue of principle-oriented approach in the teach-learning and assessment of neuroanatomy is a valid issue to be addressed in the undergraduate curriculum planning and implementation. EWMCJ Vol. 12, No. 1&2, January-July 2024: 88-93